Pengaruh Kebijakan Dividen, Leverage, Earning Volatility, dan Volume Perdagangan terhadap Volatilitas Harga Saham pada Perusahaan Sektor Finance yang Terdaftar di BEI Tahun 2014-2018 - Utami, Ayuda Rizkya; Purwohandoko, Purwohandoko (Jurnal Ilmu Manajemen, 2021)
This study aims to determine the effect of dividend policy, leverage, earning volatility, and trading volume on stock price volatility. This research is causality and uses quantitative data obtained by the purposive sampling method. There are 17 companies as research samples. The data analysis technique used is multiple linear regression. This study’s object is a company listed in the Finance sector in the Indonesia Stock Exchange for the period 2014 - 2018. The data used from financial reports, annual reports, and a summary of listed companies’ performance. The research analysis method uses a multiple linear regression with IBM SPSS version 25 software. The study results found that dividend payout ratio and dividend yield were a significant positive effect on stock price volatility. While leverage, earning volatility, and trading volume does not affect stock price volatility.